KEBIJAKAN PENETAPAN RETRIBUSI SERTA KONTRIBUSINYA TERHADAP PENDAPATAN ASLI DAERAH (SEBUAH KASUS DI KOTA CIMAHI) - Nugraha1, Nugraha1 (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2005)
To comply with the expenditures, autonomous local government often puts efforts to raiselocal revenues through retributions. However, this should be done cautiously because the retributions citizens pay should be compliant with the public services citizens gain. Therefore, local government may procure two approaches. First, local government reorientates the retribution-taking itself. Second, local government re-allocates the expenditure posts.